Legal Significance of Environmental Protection in Foreign Investments Law - Divljak, Drago (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Abstract: The paper presents the analysis of conceptual interaction between foreign investments and environmental protection, as well as its legal repercussions. A part of the paper has been directed towards critical review of the attempt of legal regulating of these relationships at an international level. A special attention was paid to the treatment of the environment in our foreign investments law. It can be concluded that the dominant paradigm of the future direction of development in this field is going to be the strengthening of the bond between international investments and environmental protection. It is insisted on the attitude that our law needs to approach adequately to the matter of legal valorisation of the environmental protection issue. This requires the creating of a complex, coherent approach that should be based on adequate legal superstructure and amendments to the existing Law on Foreign Investments. The main direction of changes implies that the current obligation of foreign investors in this field should be raised onto a higher level and foreign investments should be placed in the function of accomplishing of the concept of sustainable development. However, such an approach has to be accompanied by appropriate mechanism of control and supervision in the given field, if its full effectiveness is to be achieved.
Keywords: our law; legislation; sustainable development; international investments; foreign investments; environmental protection